Reading in English as a Second Language: A Review - Osman, Safiah (Journal of Modern Languages, 2017)
This paper reviews a number of research studies which have examined various aspects of second language reading. The focus of the paper has mainly been on the research interest of those who are concerned with potential exclamatory variables which may explain how ESL learners comprehend textual material written in English, the target language. The review reveals that more attention needs to be directed towards the specific role of prior knowledge. A better understanding of the role of prior knowledge, in addition to other variables, can offer useful insights to teachers and educators as to what constitues difficulty in comprehending English texts by non-native speakers of the language.